Kraftfoderstation till hästar - Berg, Susanna (2005)
The German equine housing system, HIT Active Stable™, are adjusted for keeping horses in groups, and are well establishes in Germany. Now the system attracts attention here in Sweden. The purpose of this study was to investigate if the horses have any be-haviours need of free access to roughages like straw or hay, after they have been visit the concentrate feeding station. A study was carried out at family Krohn's active stables in Bönningstedt, Germany. They kept 33 horses together in one group with 13 ponies and 20 standard breed horses in different size and ages. After a horse has visit the concentrate feeding station, the horse was studied during 10 minutes in order to see if the horse chose to continue eating straw or hay. The study showed that 31 % of the horses chose to continue eating straw within 10 min-utes. Of 216 visits in the concentrate feeding station during the study totally 57 % of the horses chose to continue to eat roughages. Considering the results of the study the conclusion are that horses have a need to eat roughage after a visit in the concentrate feeding station. Straw are also a good option for the horses because the forage stations are highly occupied during certain periods. Straw fed reduce aggression among horses in association to feeding station, and give the horses the possibility to natural feeding behaviour.